2023
DOI: 10.5114/ada.2022.117998
|View full text |Cite
|
Sign up to set email alerts
|

Compositional differences between gut microbiota of adult patients with asthma and healthy controls

Abstract: Introduction: Asthma is a complex and multifactorial disorder, with severe public health implications. Over the last several years, our knowledge in the field of human gut microbiota has expanded and allowed us to understand its crucial role in the development of many diseases. Aim: To analyse the nature of human gut microbiota patterns among patients with asthma compared to healthy controls. Material and methods: Composition of the complex gut microbiota was analysed in faecal samples from 13 asthma patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The results showed significant differences in the human gut microbiome composition between asthma patients and the healthy control group at the genus and species level. Patients with asthma showed a significantly greater population of Parabacteroides, Paenibacillus, Sulfurimonas, and Lachnoclostridium, while the healthy group had a greater population of Faecalitalea, Haemophilus, Syntrophothermus, Methanocella, and Geobacter [147].…”
Section: Dysbiosis In Asthmamentioning
confidence: 94%
See 1 more Smart Citation
“…The results showed significant differences in the human gut microbiome composition between asthma patients and the healthy control group at the genus and species level. Patients with asthma showed a significantly greater population of Parabacteroides, Paenibacillus, Sulfurimonas, and Lachnoclostridium, while the healthy group had a greater population of Faecalitalea, Haemophilus, Syntrophothermus, Methanocella, and Geobacter [147].…”
Section: Dysbiosis In Asthmamentioning
confidence: 94%
“…Numerous research groups have demonstrated alterations in the GM of healthy subjects compared to those of asthma patients in terms of composition and diversity [147][148][149]. In the study of Zou et al [149] faecal samples were collected from 20 healthy subjects and 47 newly diagnosed asthmatic patients.…”
Section: Dysbiosis In Asthmamentioning
confidence: 99%
“…Hoffmann et al [30] conducted a study to compare the composition of gut microbiota between patients with asthma and healthy individuals. The study included 20 samples, with 7 from healthy patients and 13 from asthmatic patients.…”
Section: Relationship Between Gastrointestinal Microbiota Dysbiosis A...mentioning
confidence: 99%
“…The original “hygiene hypothesis” has been further substantiated and refined considering contemporary lifestyle changes, such as increased rates of cesarean section, elevated utilization of antibiotics, widespread adoption of formula feeding, and alterations in modern dietary patterns, all of which have significantly impacted the components of the intestinal microbiome [ 5 , 6 ]. Both gut flora dysbiosis and respiratory flora dysbiosis have been reported to be linked to the development of the immune system, and their association with the progression of asthma is also noteworthy [ 7 ]. In recent years, the integration of interdisciplinary approaches and advanced scientific tools into the asthma research has enhanced our comprehension of the condition.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the terms microbiome and microbiota are interchangeably utilized in the literature [ 13 , 14 ]. In recent years, it has been consistently shown that the intestinal microbiota, respiratory microbiota, and skin microbiota are closely associated with the progression of asthma [ 7 , 13 , [15] , [16] , [17] , [18] , [19] , [20] ]. The microbiomes of different anatomical sites do not affect the progression of asthma independently, while the microbiomes across various anatomical sites are interconnected and engage in mutual interactions.…”
Section: Introductionmentioning
confidence: 99%